Anaerococcusmarasmi sp. nov., a new bacterium isolated from human gut microbiota. (May 2020) - Tall, M.L.; Pham, T.P.T.; Bellali, S.; Ngom, I.I.; Delerce, J.; Lo, C.I.; Raoult, D.; Fournier, P.-E.; Levasseur, A.
Abstract: Anaerococcus marasmi sp. nov. strain Marseille-P3557 T is a new species isolated from a stool of a Nigerian child with marasmus. The genome of Marseille-P3557 T was 2 130 060 bp long (35.4% G + C content). The closest species based on 16S ribosomal RNA sequence was Anaerococcus prevotii strain 20548, with 97.6% sequence similarity. Considering phenotypic features and comparative genome studies, we propose the strain Marseille-P3557 T as the type strain of Anaerococcus marasmi sp. nov., a new species within the genus Anaerococcus .